(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
This paper examines pro-Ottoman historical writing in Yemen during the 16th and 17th centuries. It analyzes key texts-such as al-Barq al-Yamānī by al-Nahrawālī, al-Futūḥāt al-Murādiyya by Ibn Dāʿir, and al-Iḥsān by al-Mawzaʿī-that portray the Ottoman Empire as a legitimate Islamic power and the Zaydi imams as rebels. These works function not only as chronicles, but also as ideological instruments that sought to reinforce Ottoman political legitimacy in the region. The study highlights the ways in which historical narratives were shaped by religious and political competition. It also finds that some texts, while overwhelmingly supportive, contain subtle critiques of the administration of the Ottoman state and the practices of some of its local governors. The study calls for a critical reading of these sources in order to understand their role in shaping historical memory and political authority in Ottoman Yemen